In memoriam: John Lisman – commentaries on CaMKII as a memory molecule - Bear, Mark F. (Mol Brain, 2018)
Shortly before he died in October 2017, John Lisman submitted an invited review to Molecular Brain on ‘Criteria for identifying the molecular basis of the engram (CaMKII, PKMζ)’. John had no opportunity to read the referees’ comments, and as a mark of the regard in which he was held by the neuroscience community the Editors decided to publish his review as submitted. This obituary takes the form of a series of commentaries on Lisman’s review. At the same time we are publishing as a separate article a longer response by Todd Sacktor and André Fenton entitled ‘What does LTP tell us about the roles of CaMKII and PKMζ in memory?’ which presents the case for a rival memory molecule, PKMζ.